Early Evolution of Transcription Systems and Divergence of Archaea and Bacteria - Lei, Lei; Burton, Zachary F. (Frontiers in Molecular Biosciences, 2021)
DNA template-dependent multi-subunit RNA polymerases (RNAPs) found in all three domains of life and some viruses are of the two-double-psi-beta-barrel (DPBB) type. The 2-DPBB protein format is also found in RNA-dependent RNAPs and a major replicative DNA-dependent DNA polymerase (DNAP) from Archaea (PolD). The 2-DPBB family of RNAPs and DNAPs probably evolved prior to the last universal common cellular ancestor (LUCA). Archaeal Transcription Factor B (TFB) and bacterial sigma factors are homologs and are comprised of strings of helix-turn-helix units. The consequences of TFB-sigma homology are discussed in terms of the evolution of archaeal and bacterial core promoter structures. Archaea appear to be more similar to LUCA than Bacteria. It appears that evolution of bacterial sigma factors was of fundamental importance in divergence of Bacteria from Archaea, splitting the prokaryotic domains.